Method to Estimate Mechanical Properties of Glulam on Flexure Testing Based on Its Laminae Characteristics and Position - Effendi Tri Bahtiar; Naresworo Nugroho; Muh Yusram Massijaya; Han Roliandi; Rentry Augusti; Adi Satriawan (Indonesian Journal of Physics, 2011)
Glulam strength is affected by its laminae characteristics and position. Modulus of Elasticity and Modulus of Rupture of layer system (including glulam) is usually estimated by Transformed cross section (TCS) method recently. But, TCS does not follow the principal due to its contrary assumption related with the reduction of material’s plane area for laminae with lower E value and the extension of its plane area for laminae with higher E value. In fact the material properties are independent from its shape and size. Therefore, new calculation method is required. As the relevance, this paper discusses the formulation of a new method to determine the E and SR for glulam based on its laminae properties and position. E and SR calculated by TCS and new method give identical values. The new method confirms the independence of E and SR which could not be fulfilled by TCS. According to this fact, TCS could be replaced by new method. The theoretical E value was higher than its coresponding empirical value, but it has high correlation (R2=68.53%). On the contrary, the theoretical SR value was not significantly different from its coresponding empirical values, but they have poor correlation (R2=27.93%). This condition happened because of finger joint effect on the compression and tension side of the sample. Incorporating the finger joint effect into regression analysis, the equation provides very good prediction. The coefficients of determination were 99.58% and 97.19%, for E and SR respectively.